ANALISIS SISTEM INFORMASI WEB LSP UAD MENGGUNAKAN USER EXPERIENCE QUESTIONNAIRE (UEQ) - Rusydi Umar; Aulyah Zakilah Ifani; Fathia Irbati Ammatulloh; Maya Anggriani (Universitas Methodist Indonesia, 2020)
The progress of the world has been so fast that workers in various professions have increasingly needed recognition. University and Vocational School graduates need fields to test the ability of the profession they do. Ahmad Dahlan University (UAD) is one of the universities that has a professional testing institution called the UAD Professional Certification Institute (LSP). LSP UAD functions as an institution to test the professions required by prospective UAD graduates themselves. Until now, LSP UAD has ten schemes that can be tested on prospective study program graduates. To simplify the information related to the scheme, students can see on the LSP UAD website, information is also available for other LSPs and accessories. However, the UAD LSP web has not tested the satisfaction of web users such as student users. This paper was created to test user satisfaction or User Experience (UX) for users to improve information services on the web. Analysis on the UAD LSP web used the User Experience Questionnaire (UEQ) method to 15 students who had used the web as respondents. UEQ's assessment refers to six aspects, namely: efficiency, attractiveness, accuracy, clarity, novelty, and stimulation. The results of the analysis showed that the average respondent gave an impression with results above average in the aspects of clarity, accuracy, stimulation, and novelty. Meanwhile, attractiveness and efficiency get good scores.